Kecenderungan âFramingâ Media Massa Indonesia dalam Meliput Bencana Sebagai Media Event - WahyuniÃ¯Â€Âª, Hermin Indah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2008)
Mass media industries always frame their news based on their perspective and interest. This paper will examine the framing of disaster event and issues of contemporary Indonesia: the media framing on the natural disaster event (Yogyakartaâs earth quake, Mei 2006 and Padangâs earth quake, March 2007); the media framing on the disaster because of human factor (Senopati Tragedy, December 2006 and Adam Air Tragedy, January 2007); the media framing on the natural disaster because of natural and human factor (Lapindo Case, May 2006âMarch 2007). Based on framing analysis, this paper presents some interesting findins and discussion the different framing of each mass media as friends, foe, adversarial agent and empowerment agent.